Detection of diarrheagenic Escherichia coli from children with and without diarrhea in Salvador, Bahia, Brazil - Vanessa Bueris; Marcelo Palma Sircili; Carla Romano Taddei; Maurilio Fernandes dos Santos; Marcia Regina Franzolin; Marina Baquerizo Martinez; Suzana Ramos Ferrer; Mauricio Lima Barreto; Luiz Rachid Trabulsi (Memorias do Instituto Oswaldo Cruz, 2007)
We identified different diarrheagenic (DEC) Escherichia coli pathotypes isolated from 1,207 children with and without acute endemic diarrhea in Salvador, Bahia, Brazil collected as part of a case-control study. Since the identification of DEC cannot be based on only biochemical and culture criteria, we used a multiplex polymerase chain reaction developed by combining five specific primer pairs for Enteropathogenic Escherichia coli (EPEC), Shiga toxin-producing E. coli/ Enterohaemorrhagic E. coli (STEC/EHEC), Enterotoxigenic E. coli (ETEC) and Enteroaggregative E. coli (EAEC) to detect these pathotypes simultaneously in a single-step reaction. In order to distinguish typical and atypical EPEC strains, these were tested for the presence of EAF plasmid. The prevalence of diarrheagenic E. coli in this sample of a global case-control study was 25.4% (259 patients) and 18.7% (35 patients) in the diarrhea group (1,020 patients) and the control group (187 patients), respectively. The most frequently isolated pathotype was EAEC (10.7%), followed by atypical EPEC (9.4%), ETEC (3.7%), and STEC (0.6%). Typical EPEC was detected only in one sample. The prevalence of the pathotypes studied in children with diarrhea was not significantly different from that in children without diarrhea.